Understanding Organizational Readiness for Green Supply Chain Management in Public Sector Supply Chains - Izzaturrahman, Muhammad; Islam, Azmi Muhammad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The growing emphasis on environmental sustainability has encouraged organizations to integrate environmental considerations into their supply chain operations through the adoption of Green Supply Chain Management (GSCM). However, the successful implementation of GSCM largely depends on the internal readiness of organizations to support such initiatives. This study aims to analyze the organizational readiness for implementing GSCM at PT PLN (Persero) Headquarters, Indonesia’s state-owned electricity company. The research employs a qualitative descriptive approach to explore organizational conditions related to material planning and supply chain information system integration. Data were collected through participant observation during an internship period, unstructured interviews with personnel involved in supply chain management, and analysis of internal organizational documents. The findings indicate that the overall readiness for GSCM implementation within the organization can be categorized as moderate. Key challenges include inconsistencies in information sharing across organizational units and limited integration between digital systems, which affect the efficiency and accuracy of material planning processes. In addition, supplier relationships remain largely focused on short-term operational needs rather than long-term sustainability collaboration. Nevertheless, strong managerial commitment and existing technological infrastructure provide important opportunities for strengthening GSCM implementation in the future. This study contributes to the literature by providing empirical insights into organizational readiness for GSCM within the context of a public sector utility, highlighting the importance of aligning organizational processes, digital systems, and supply chain relationships to support sustainable supply chain practices.